EATING BEHAVIOR DISORDERS, ANXIETY, DEPRESSION, AND BODY DISSATISFACTION: A COMPREHENSIVE ANALYSIS AMONG OBESE WOMEN - Kuchkarov Humoyun Nurali o’g’li; N. F. Yadgarova (Modern American Journals, 2025)
Obesity is one of the pressing issues in modern medicine and psychology, directly linked not only to metabolic syndromes but also to mental health disorders. Studies indicate that individuals with excess weight may exhibit high levels of eating behavior disorders (emotional, external, and restrictive), as well as anxiety, depression, and body image dissatisfaction. Obese women who have not undergone bariatric surgery represent a particularly vulnerable group to these factors. An in-depth study of their psychological state is crucial for developing individualized treatment and psychoprophylaxis plans.
Keywords: Obesity, eating disorders, emotional eating, anxiety, depression, dissatisfaction with body shape